VARIASI BAHASA MINANGKABAU PADA LIRIK-LIRIK LAGU MINANG: SEBUAH GAMBARAN RETENSI DAN INOVASI BAHASA - Djonnaidi, Silvia (Puitika, 2015)
This article is aimed to explain the variations of Minangkabau language in the lyrics of Minang’s Songs in the 1950-s and 1990-s. The analysis focuses on variations related to the retention and inovation form. The scope of the analysis are the variations of Minangkabau languange in all aspects whether the variations in form (fonology, morphology, and lexical) or variations in meaning (semantic). The method in collecting the data is non participant observational method with the note-taking technique. The method in analyzing the data is referential method. In order to find out languange retention and inovation, a top-down approach is also used in analyzing the data. The result of the analysis shows that there are variations of phonology, morphology, lexical, and semantic in Minang’s songs during 1950-s and 1990-s. The differences in both of the era are seen from the aspect of phonology and diftong. Another differences are found in variations of lexical and semantic. Minang’s songs in 1990-s have lots of lexical and semantic variations than the era of 1950-s. Based on the process of reconstruction, it is observed that Minang’s songs have some changes in the aspects of phonology, morphology, lexical and semantic. The songs in 1950-s tend to maintain the use of the words which have been heritaged from the relic form of Minangkabau language. On the other hand, the songs in 1990-s mostly have the innovation in internal and external aspects whether they are lexical or semantic innovation. Innovation tends to occur on cultural vocabularies, while the basic vocabularies tends to maintain their relic forms. Keywords: variations of language, phonology, morphology, lexical, semantic, retention,innovationABSTRAK Artikel ini bertujuan untuk menjelaskan variasi bahasa Minangkabau pada lirik lagu Minang di era 1950-an dan 1990-an. Analisis difokuskan pada variasi yang memperlihatkan bentuk retensi dan inovasi. Ruang lingkup penganalisisan adalah variasi bahasa Minangkabau pada semua aspek, baik itu variasi bentuk (fonologi, morfologi, dan leksikal), ataupun variasi makna (semantik). Metode pengumpulan data adalah metode simak tidak libat cakap dengan teknik catat. Metode penganalisisan data adalah metode padan. Hasil analisis data menunjukkan bahwa terdapat variasi fonologis, morfologis, leksikal, dan semantis di dalam lagu minang era 50-an dan 90-an. Perbedaan dari kedua era ini dapat dilihat pada aspek fonologis dan diftong. Perbedaan lainnya ditemukan pada variasi leksikal dan semantis. Lagu Minang di era 90-an memiliki lebih banyak variasi leksikal dan semantis dibandingkan dengan lagu Minang era 50-an. Berdasarkan proses rekonstruksi, dapat diamati bahwa lagu Minang memiliki beberapa perubahan pada aspek fonologis, morfologis, leksikal, dan semantis. Lagu-lagu di era 50-an cenderung mempertahankan penggunaan kata-kata yang merupakan warisan dari bentuk relik bahasa Minangkabau. Di sisi lain, lagu-lagu era 90-an kebanyakan mengalami inovasi pada aspek internal dan eksternal, baik itu inovasi leksikal maupun semantis. Inovasi tersebut cenderung terjadi pada kosakata budaya, sedangkan untuk kosakata dasar cenderung mempertahankan bentuk reliknya.  Kata kunci: variasi bahasa, fonologi, morfologi, leksikal, semantik, retensi, inovasi